PERTANGGUNGJAWABAN NEGARA TERHADAP KASUS KEBAKARAN HUTAN DAN LAHAN DI INDONESIA MENURUT PRINSIP ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION - Heny Rosida (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Forest fire is a phenomenon that is often encountered in various countries, including Indonesia. Indonesia as a country that is often hit by forest fires annually. Forest fires can arise from intentional or unintentional factors. The impact that can be caused by the existence of forest fires is in terms of air pollution which has an impact on other countries. This study will analyze and examine various legal aspects of how the state is responsible, in this case, Indonesia for the losses suffered by other countries. The formulation of the problem in this research is about how to account for the aspects of the international law contained in the AATHP, and how to analyze the settlement of international law on fire cases in Indonesia. The method used in this paper is normative juridical. The data and the field facts presented in this paper are obtained from printed and online sources. This study confirms that forest fire is the responsibility of the Indonesian state in the perspective of international law, one of them is in the arrangement of the Asean Agreement On Transboundary Haze Pollution (AATHP).Keywords: AATHP; Forest and land fires; State responsibility